The blind and deaf adolescents` point of view about swimming as a social phenomenon - Statkeviciene, B.; Gylyte, S. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
The objective of the study was to determine the opinion of the visual impaired adolescents` and deaf adolescents towards swimming as a social phenomenon. The tasks were 1. Determine the outlook of adolescents who have visual or hearing handicap toward their potential to learn how to swim. 2. To compare the different opinions of visual and hearing handicapped adolescents about swimming as a discipline of athletics. 3. To determine the level of knowledge about swimming is regarded by visual and hearing handicapped adolescents.